Color Doppler Evaluation of Arterial Resistive Index in Infantile Hemangioma: A Useful Parameter to Monitor the Response to Oral Propranolol? - Parapatt, George Koshy; Oranges, Teresa; Paolantonio, Guglielmo; Ravà, Lucilla; Giancristoforo, Simona; Diociaiuti, Andrea; Hachem, May El; Rollo, Massimo (Frontiers in Pediatrics, 2021)
Infantile hemangioma (IH) is the most common benign vascular tumor in childhood. In more than 85% of all cases IHs undergo spontaneous involution, but nearly 10-12% of IHs develop complications and require immediate therapy. Oral propranolol is currently the first-line treatment for IHs. Color Doppler ultrasound is the gold standard in the diagnosis of deep IH and it is used to evaluate the morphological change and the modification of vascularization that occur during its evolution and treatment. To date, only few data in the literature described the changes of intralesional arterial resistive index (RI) during treatment with propranolol, particularly some Authors have shown an increase of intralesional arterial RI in IHs with clinical regression during treatment with propranolol. The objective of this paper is to evaluate changes of RI of the intralesional arteries of the IHs during the treatment with oral propranolol. We retrospectively analyzed a total of 64 IHs in 60 patients treated with oral propranolol with a good clinical response. Gray scale ultrasonography and color Doppler imaging were performed before and during the therapy. Intralesional RIs were measured before and during the treatment. For each lesion we recorded the RI values, and then we calculated the mean RI value for any single lesion. We compared the mean RI value observed at the baseline with the mean RI value of the last detectable sampling at color Doppler. We also compared between them the mean RI values observed during intermediate ultrasound. RI values where compared in 44 lesions with at least two significant samplings of RI. In the 44 lesions compared, we did not find statistically significant variations in the mean RI values between the baseline control and the values recorded at the last post-treatment control. The time trend of mean RI values of the intermediate color Doppler analysis performed between the first pre-treatment control and the last measurable control did not show any statistically significant variation in the trend of mean RI values. Contrarily to what has been described by some Authors in our experience we have not observed an increase of RI in IHs treated with oral propranolol.